A comparison between metaheuristic-based and solver-based methods to solve routing problem based on sectorization - Teymourifar, Aydin (2021)
This study involves the division of a region into smaller units, based on sectorization, and a route determination for each of them. The routing problem of each unit is defined as a basic traveling salesman problem (TSP). Different implementations of a widely used method to solve TSP are compared. The method is based on a mixed-integer linear programming model, in which after finding an initial solution, a sub-tour elimination process is done iteratively. The implements of the method use some metaheuristics and solvers, which are available in libraries and toolboxes of MATLAB and Python. The implementations are compared in terms of results and solution times. Suggestions to solve large-scale problems are presented, which are derived from the results.